Analysis Of Satisfaction Mustahik Rumah Sehat Baznas Jakarta - Siti Masturoh; Veithzal Rivai Zainal; Aziz Hakim (Dinasti Publisher, 2023)
The realization of a healthy state is the desire of all parties. Not only by individuals, but also by families, groups and even communities. In order to realize optimal public health status, various efforts must be implemented, one of which is to provide health services. With the increasing level of education and the socio-economic condition of the community, the needs and demands of the community for health appear to be increasing as well. To be able to meet these needs and demands, there are no other efforts that can be made, except to provide the best possible health services. In accordance with the mandate of Article 6 Law 23 of 2011 concerning the management of Zakat, the National Zakat Amil Agency includes the functions of planning, collection, distribution and utilization, reporting and accountability. In carrying out the distribution of zakat, one of the areas that becomes one of the concentrations of BAZNAS is the health sector which is one of the basic needs of Mustahik. The role of BAZNAS in facilitating health needs and supporting the government's obligation to provide health services is carried out by carrying out a distribution process in the health sector.